A Composite Web Design Structure for Online Tennis Court Payment System - Kassim, Murizah; Syazwani Mohd Pakhrudin, Nor; Husna Awang, Aziati; Ku Haroswati Che Ku Yahaya, Cik; Ya’acob, Norsuzila (International Journal of Engineering and Technology, 2019)
This paper presents the development of composite web design structure for online booking tennis court system. Problems identified that IR 4.0 for sports facilities is needed where less of sports owner implemented to facilitated effective management. Customer navigation has been a challenge to design well-structured websites to manage their facilities. The different understanding of the web developer and the user is considerably different that caused for poor website design.Â The objective for this research is to provide a simple online reservation system for a tennis court where customers are easy to access to the tennis court facilities. Analysis of the customer satisfaction is retrieved based on the designed system. The system was designed with functions that follow specific requirement, including userâ€™s registration and login, online booking, online payment, QR code, composite web design structure and database construction. The system was developed using CMS (Content Management System) with Joomla applications and XAMPP web software. XAMPP is free open source added with a combination of Apache, PHP and MySQL. The Google spreadsheet was used to create QR code. Informational databases like time booking, court available and online payment are designed. Data collection on the web page on the running composite webpage has been analyzed and results on rates of the portal, the player’s booked, time booking, customers by ages and genders, Indoor and Outdoor booking are presented. Data shows an increase in booking daily from 7 am to 10 pm compared to last year based on the easy booking system with a composite web design structure of online payment prototype system that has been developed. This research presents an impact on IR 4.0 development towards managing sports facilities with recent trends and human health activities. Â Â